Polymyalgia rheumatica: 125 years of progress?. Issue 4 (November 2014) - Rooney, Patrick J; Rooney, Jennifer; Balint, Geza; Balint, Peter
Objectives: On the 125th anniversary of the first recognised publication on polymyalgia rheumatica, a review of the literature was undertaken to assess what progress has been made from the point of view of the clinical care of affected patients. Methods: The authors searched Medline and PubMed using the search terms 'polymyalgia rheumatica', 'giant cell arteritis' and 'temporal arteritis'. As much as possible, efforts were made to focus on studies where polymyalgia rheumatica and giant cell arteritis were treated as separate entities. The selection of articles was influenced by the authors' bias that polymyalgia rheumatica is a separate clinical condition from giant cell arteritis and that, as yet, the diagnosis is a clinical one. Apart from the elevation of circulating acute phase proteins, which has been recognised as a feature of polymyalgia rheumatica for over 60 years, the diagnosis receives no significant help from the laboratory or from diagnostic imaging. Results: This review has shown that, following the recognition of polymyalgia as a distinct clinical problem of the elderly, the results of a considerable amount of research efforts including those using the advances in clinical imaging technology over the past 60 years, have done little to change the ability of clinicians to define the disease more accurately. Since the introduction of corticosteroids in the 1950s, there has been also very little change in the clinical management of the condition. Conclusions: Polymyalgia rheumatica remains a clinical enigma, and its relationship to giant cell arteritis is no clearer now than it has been for the past 125 years. Diagnosing this disease is still almost exclusively dependent on the clinical acumen of a patient's medical attendant. Until an objective method of identifying it clearly in the clinical setting is available, uncovering the aetiology is still unlikely, and until then, preventing the pain and stiffness of the disease while avoiding the problems of prolonged exoposure to corticosteroids is likely to remain elusive or serendipitous.